The Effect of Using Educandy/Kahoot!-Based Interactive Learning Media on English Vocabulary Learning Outcomes among Students at SMPN 3 Kepahiang Regency - Barata Harsena Dewa; Saipul Saipul (Utami Publisher, 2026)
This study aims to examine the effect of using gamification-based interactive learning media (Educandy and Kahoot!) on students' English vocabulary mastery at SMPN 3 Kepahiang Regency. This study employed a quasi-experimental method with a Non-equivalent Control Group Design. The research population consisted of all seventh-grade students at SMPN 3 Kepahiang Regency in the 2025/2026 academic year. The sample was selected using purposive sampling and consisted of two classes, namely Class VII.A (n = 30) as the experimental class, which was taught using Educandy/Kahoot! media, and Class VII.B (n = 30) as the control class, which used conventional teaching methods. Data on vocabulary mastery were collected through objective tests (pretest and posttest). The results of the analysis showed that the mean posttest score of the experimental class (82.60) was significantly higher than that of the control class (68.20). The independent samples t-test yielded a calculated t-value of 6.841 with a p-value (Sig. 2-tailed) of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The mean N-Gain score of the experimental class was categorized as effective (0.58; moderate/high category), compared with the control class (0.25; low category). It can be concluded that the integration of Educandy/Kahoot!-based interactive media has a significant positive effect on improving students' English vocabulary learning outcomes.